Total Synthesis and Cytotoxic Activity of 7-O-Methylnigrosporolide and Pestalotioprolide D - Thiraporn, Aticha; Iawsipo, Panata; Tadpetch, Kwanruthai (Synlett, 2022)
A convergent total synthesis of 7-O-methylnigrosporolide and pestalotioprolide D has been accomplished in 17 linear steps and overall yields of 1.7% and 2.6%, respectively, starting from (S)-propylene oxide and (S)-benzyl glycidyl ether. Our synthesis exploited an acetylide addition and a Shiina macrolactonization to assemble the macrocycle, a Lindlar reduction, and Wittig and Still–Gennari olefinations to construct the three alkene groups, as well as a Jacobsen hydrolytic kinetic resolution to install the stereogenic center. The selection of the silyl protecting group of the C-4 alcohol was crucial for the final deprotection step. Our synthesis also led to a hypothesis that pestalotioprolide D might be an artifact of 7-O-methylnigrosporolide. The cytotoxic activities of the two synthetic compounds against six human cancer cell lines were evaluated. Synthetic pestalotioprolide D showed more potent cytotoxic activity than 7-O-methylnigrosporolide against all the cancer cell lines tested, and the SiHa cervical cancer cell line was the most sensitive to both synthetic compounds.
Keywords: total synthesis; cytotoxicity; macrolactones; 7-O-methylnigrosporolide; pestalotioprolide D